Optimalisasi Media Sosial untuk Pemasaran Wellness Tourism Berbasis Komunitas Lokal - Nerys Lourensius L. Tarigan; Edy Prayitno; Ferhadius Endi; Sugiman Sugiman; Sri Setyowati (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Wellness tourism based on local communities in Yogyakarta has significant potential for development through social media marketing, but it is often hindered by limited digital skills and resources. This study aims to analyze the effectiveness of social media in promoting wellness tourism by local communities and to formulate optimal strategies to enhance destination visibility. Using a qualitative approach, this study analyzes content from 10 Instagram and TikTok accounts managed by local communities in Yogyakarta (Sleman, Bantul, and Yogyakarta city) over the period of November 2024–April 2025, complemented by interviews with five account managers. The results show that interactive content (6.5%) and visual content (5.2%) generate higher engagement rates compared to narrative content (3.8%). Peak engagement occurred in December 2024 and April 2025, coinciding with holiday periods. Effective strategies include regular posting, collaboration with local influencers, and highlighting local culture such as jamu therapy. The main challenges are limited editing skills and promotional budgets. This study recommends increasing interactive content, producing high-quality visuals, and providing digital skills training to support the economic sustainability of local communities through wellness tourism.